Effect of Inflation, Interest Rates, Exchange Rates, Gross Domestic Product, and Good Corporate Governance on the Value of Consumer Goods Companies Listed on the Indonesia Stock Exchange - Angelin Effendi; Viviana Indri; Ninta Katharina (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is to analyze effect of inflation, interest rates, exchange rates, gross domestic product, and good corporate governance on the value of consumer goods companies listed on the Indonesia Stock Exchange. The form of this research is quantitative and descriptive. The population used is 57 Consumer Goods Companies listed on the Indonesia Stock Exchange on the 2017-2020. This research uses purposive sampling. The total number of data observations in this study is 84 observation data. The research data analysis method is multiple linear regression analysis. Multiple linear regression analysis using partial test (t) and simultaneous test (F). The results show that inflation has a positive and insignificant effect on the value of consumer goods companies listed on the Indonesia Stock Exchange. Interest rates has a positive and insignificant effect on the value of consumer goods companies listed on the Indonesia Stock Exchange. Exchange rates has a positive and insignificant effect on the value of consumer goods companies listed on the Indonesia Stock Exchange. Gross domestic product has a negative and insignificant effect on the value of consumer goods companies listed on the Indonesia Stock Exchange. Good corporate governance has a positive and insignificant effect on the value of consumer goods companies listed on the Indonesia Stock Exchange. Inflation, interest rates, exchange rates, gross domestic product, and good corporate governance simultaneously have a significant effect on the value of consumer goods companies listed on the Indonesia Stock Exchange.